Periodization of General Elections: Ideas and Refinements in Indonesia - Muhammad Mutawalli; Naswar Naswar; Aminuddin Ilmar; Georges Olemanu Lohalo (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2023)
General election is one part of the practice of democracy in Indonesia. In this case, the general election is a manifestation of people's sovereignty. In general, the principles of elections include the principles of direct, public, free, confidential, honest and fair. This research seeks to explore legal constructions related to the periodic principle of general elections which must be held periodically every five years, which is a separate principle in general elections. This research is normative legal research with a statutory and conceptual approach. The results of the study confirm that to achieve and ensure that general elections are held a justice process and proportionally, the orientation of legal construction on the periodic principle has actually been explicitly stated in the 1945 Constitution of the Republic of Indonesia and is based on a systematic interpretation. In this case, in terms of periodic aspect orientation, it is part of the general election principle that is obligatory and must be implemented. This has the implication that the principles of general elections include the principles of direct, general, free, confidential, honest and fair, and must be held periodically for five years. In this case, the principle of periodicity occupies an important position in the holding of general elections.